Characteristics and Performance of Nanozinc Oxide/Mesoporous Silica Gel Photocatalytic Composite Prepared by a Sol-Gel Method. (9th March 2015) - Xu, Hang; Yu, Tianlong; Liu, Yi
Abstract : Nano-ZnO loaded mesoporous SiO2 was prepared by sol-gel technology as a photocatalytic composite. XRD, SEM, TEM, EDX, and N2 sorption isotherms were used to characterize the nano-ZnO/mesoporous SiO2 . Acid Red 18 was used as simulated pollutant to determine the photocatalytic performance of nano-ZnO/mesoporous SiO2 under ultraviolet light and solar light. The results showed that 6.4 nm ZnO was obtained and immobilized on mesoporous SiO2 . Compared to the mesoporous SiO2, the surface area and average pore width of nano-ZnO/mesoporous SiO2 were reduced by 12 m 2 /g and 0.7 nm, respectively. 50% ZnO content in a composite calcinated at 200 ∘ C exhibited the best photocatalytic activity. The removal of Acid Red 18 under solar irradiation was 10% higher than ultraviolet light.